Oral lipid-based drug delivery systems - an overview - Sandeep Kalepu; Mohanvarma Manthina; Veerabhadhraswamy Padavala (Elsevier, 2013)
The formulation of drugs is carried out with the principle objective of enhancing their bioavailability. Poorly water soluble drugs are challenging for the formulation scientists with regard to solubility and bioavailability. Lipid-based drug delivery systems (LBDDS) are one of the emerging technologies designed to address such challenges. Encapsulating or solubilizing the drug in lipid excipients can lead to increased solubilization and absorption, resulting in enhanced bioavailability. Recent advances in these formulation technologies have led to the successful commercialization of lipid-based formulations. This review provides a comprehensive summary and characterization of lipid-based formulations, especially for oral delivery, from both physicochemical and biopharmaceutical perspectives. This review also focuses on the processing techniques necessary to obtain solid lipid-based formulations for oral delivery, along with a brief discussion of lipid excipients and their characterization.